PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN BADAN USAHA MILIK NEGARA YANG TERDAFTAR DI BEI PERIODE 2019 - 2021 - Marisha Khanida; Tituk Diah W (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
The purpose of this study are to examine the effect of independent board of commissioners, audit committee, managerial ownership, public ownership, and government ownership on financial performance using agency theory. This research uses quantitative methods. The subject of this study is BUMNcompanies, with the study population being all BUMN companies listed on the Indonesia Stock Exchange.This research is classified as quantitative research. The type of data used is secondary data in the form of annual financial statements of BUMN companies listed on the Indonesia Stock Exchange in the period 2019-2021. The technique used for sampling is the purposive sampling method and the method used for hypothesis testing is multiple linear regression analysis. The results showed that the independent commissioner variable had a significant positive effect on the company's financial performance, the audit committee had a significant positive effect on the company's financial performance, managerial ownership had no significant positive effect on the company's financial performance, public ownership had a significant positive effect on the company's financial performance, and government ownership significant positive effect on the company's financial performance.